Perfluorooctane sulfonates induces neurobehavioral changes and increases dopamine neurotransmitter levels in zebrafish larvae. (June 2022) - Wu, Luyin; Dang, Yao; Liang, Li-Xia; Gong, Yan-Chen; Zeeshan, Mohammed; Qian, Zhengmin; Geiger, Sarah Dee; Vaughn, Michael G.; Zhou, Yang; Li, Qing-Qing; Chu, Chu; Tan, Ya-Wen; et al.
Abstract: It has been reported that exposure to perfluorooctane sulfonates (PFOS) causes behavioral abnormalities in zebrafish larvae, but the possible mechanisms underlying these changes remain unexplored. In this study, zebrafish embryos (2 h postfertilization, 2-hpf) were exposed to PFOS at different concentrations (0, 0.032, 0.32 and 3.2 mg/L) for 120 h. Developmental endpoints and the locomotion behavior of larvae were evaluated. Reactive oxygen species (ROS) levels, dopamine contents, several genes and proteins related to neurodevelopment and dopamine signaling were examined. Our results indicate that increased ROS levels in the zebrafish larvae heads may be causally associated with neurodevelopment damage. Meanwhile, brain-derived neurotrophic factor (BDNF) and alpha1-Tubulin (α1-Tubulin) protein contents were significantly increased, which may be a compensatory mechanism for the impaired central nervous system. PFOS-induced locomotor hyperactivity was observed in the first light phase and dark phase at the 0.32 and 3.2 mg/L of PFOS. Upregulation of dopamine-related genes tyrosine hydroxylase ( th ) and dopamine transporter ( dat ) associated with increased dopamine contents in the 3.2 mg/L of PFOS. In addition, protein expression of TH and DAT were noted at the 0.32 and 3.2 mg/L of PFOS concentrations. Our results suggested that PFOS induces neurobehavioral changes in zebrafish larvae, possibly by perturbing a dopamine signaling pathway. In addition, PFOS induced development damage, such as increased malformation rate and shorter body length. Graphical abstract: Image 1 Highlights: PFOS induced ROS generation in larvae head. PFOS induced neurobehavioral in larvae. mRNA and protein levels involved in dopamine pathway were significantly changed. PFOS induced neurobehavioral in larvae, which might be to a dopamine pathway.